PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK POTENSI GARAM PAMEKASAN UNTUK SISWA KELAS IV SEKOLAH DASAR - Farhan Amnan Mullisi; Conny Dian Sumadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Lack of use of interesting learning media in learning activities so that students become passive. This research aims to determine the validity of the pop up book learning media on the potential of Pamekasan salt for fourth grade elementary school students which can be seen from the validation of material and media experts. The type of research used is development research with the ADDIE model. However, this research was only at the Development stage. The subjects in this research were fourth grade students at SD Negeri Ponteh 1. The data collection techniques used in this research were questionnaires, observation, interviews and documentation. The analysis technique in this research uses descriptive qualitative and quantitative data analysis techniques. The research results showed that the pop up book media on the potential of Pamekasan salt, the material for changing the form of objects developed, obtained a percentage score of 87.5% in the category